Perkembangan Sistem Pemasaran Makanan Tradisional Dakak-dakak Ni Nun Nagari Simabur Kecamatan Pariangan Kabupaten Tanah Datar Tahun 2000-2019 - Miftahul Magfirah; Hendri Naldi (Jurusan Sejarah FIS UNP, 2022)
This research is a study of economic history that examines the development of traditional food marketing systems in the Dakak-dakak Ni Nun in Nagari Simabur, Pariangan District, Tanah Datar Regency from 2000-2019, the purpose of this study is to describe the beginning of the emergence of the traditional food industry in dakak-dakak Ni Nun, the development of the marketing system from 2000-2019 and obstacles encountered in using the marketing system used. In this study the method used is historical method, historical research method is the process of testing and analyzing critical history of recording and relics of the past. Imaginative reconstruction of the past based on data obtained by taking a historiographic process (historical writing). In the historiographic stage there are the first four steps are heuristics (data collection), the second is verification (source criticism), the third interpretation (interpretation) and the last historiography (historical writing). Nun where this can be seen from the increase in sales from year to year but in marketing the product there are also obstacles that are passed but Ni Nun can overcome them so that they can last until 2019.